Architectural inventory of tangible built heritage in Gingoog City planning towards tourism product development - Belotindos, Aldeah Mae B.; Pernes, Nory Loyd N. (2015)
Mindanao has a number of potential historical assets for tourism but only a few of them are established and well-known to the public. Among them are the ancestral houses in Gingoog City. Heritage tourism provides a strong incentive to preserve heritage. This study aims to place the issues of heritage conservation within the overall process of tourism development in Gingoog City. This was achieved through the identification and documentation of the architectural heritage assets and the evaluation of the tourism potential of the heritage site. There were a total of thirteen (13) ancestral houses within the Poblacion District, all in need of proper conservation in order to preserve its authenticity. Results from the survey quantified the tourism potential value of the heritage site to be 0.760 or 76% which would conclude the destination to have above average tourism potential. With regards to the architectural heritage, most of the respondents were interested in knowing more about its history and culture. The general attitude of tourists towards architectural heritage together with the most popular accommodation, transportation, and activities according to the survey represented the demands of the target audience. These variables were considered in proposing the tourism products and plans. A tourism strategic plan consisting of standards derived from the identified attributes can be formulated to help determine how much change is acceptable in the area before actions are taken. Further studies should also include conservation plans focusing on the interior of the heritage assets
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2015